ANALISIS PERBEDAAN KINERJA GURU PNS DENGAN GURU NON PNS PADA SMK NEGERI 7 PEKANBARU - Paramita, Adinda; ', Gimin; ', Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : One faktor that affects the quality of learning is the variable performance of teachers. Teachers have a dominant influence on the quality of learning, because the teacher is the one who is responsible for the learning process in the classroom, even as education providers in schools. In carrying out the process of teaching and learning not only to teachers are Civil Servants but applies also to the teachers of Non-Civil Servant. In carrying out the process of teaching and learning not only to teachers are civil servants but applies also to the teachers of Non-Civil Servant. On the fact that the actual performance of the teachers are still not much gets done properly, whether teachers are teachers of Civil Servants had a good performance in accordance with the rules and responsibilities of the Government or are still less well in doing performance teaching, or the performance of the teachers of Non-Civil Servants even better than on the performance of the teacher of Civil Servants. The purpose of this research is to know the difference in performance of teachers with the teachers of Non-Civil Servants and Civil Servants At State Vocational secondary school 7 of Pekanbaru. The data obtained provide a questionnaire to all teachers are Civil Servants and Non-Civil Servants who teaches at the school that is as much as 40 respondent. The data analysis techniques are used descriptive analysis and the analysis of the T- test. The results of the research there is a difference between the performance of teachers with teachers of Non Civil Servants and Civil Servants based on T-test test performed show that the significance of the value obtained from the calculation of a Non Parametric Test that is smaller than 0.004 value specified significance 0.05 (p > 0.050). Keywords : The Performance, Teachers of Civil Servants, Teachers Of Non Civil Servants